When work is punishment: Penal subjectivities in punitive labor regimes - Hatton, Erin Elisabeth (Punishment & society, 2018)
Scholars have persuasively argued that U.S. penal and welfare institutions comprise a single policy regime that has taken a punitive turn with carceral expansion and welfare contraction. Less recognized, however, is the centrality of labor to this regime. Not only has labor been the lynchpin of welfare reform with the expansion of workfare, it has also been an important yet overlooked dimension of mass incarceration, as most able-bodied American prisoners are required to work. For prisoners and welfare recipients, work is a punitive curtailment of citizenship rights, even as it is a foundation of such rights for others. This article thus conceptualizes work as a form of punishment in the penal-welfare regime. Drawing on 83 in-depth interviews with incarcerated and workfare workers, it examines these workers’ penal subjectivities—how they ideologically navigate their labor qua punishment. Through this negotiation, it finds, incarcerated and workfare workers deploy, contest, and reify the cultural narratives that justify their relegation to punitive labor regimes.